2000
DOI: 10.1523/jneurosci.20-16-06007.2000
|View full text |Cite
|
Sign up to set email alerts
|

F-Actin Is Concentrated in Nonrelease Domains at Frog Neuromuscular Junctions

Abstract: To gain insight into the role of F-actin in the organization of synaptic vesicles at release sites, we examined the synaptic distribution of F-actin by using a unique synaptic preparation of frog target-deprived nerve terminals. In this preparation, imaging of the synaptic site was unobstructed by the muscle fiber cytoskeleton, allowing for the examination of hundreds of synaptic sites in their entirety in whole mounts. At target-deprived synaptic sites F-actin was distributed in a ladder-like pattern and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 42 publications
3
38
1
Order By: Relevance
“…Similar morphologic changes were observed at synapses of the giant reticulospinal axon of the lamprey after microinjection of antibodies and peptides that disrupted synaptojanin recruitment (46). Studies of lamprey and mammalian synapses have demonstrated that synaptic vesicle clusters are surrounded by actin, suggesting that actin is the major component of the matrix present at these endocytic zones (28,29,56).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Similar morphologic changes were observed at synapses of the giant reticulospinal axon of the lamprey after microinjection of antibodies and peptides that disrupted synaptojanin recruitment (46). Studies of lamprey and mammalian synapses have demonstrated that synaptic vesicle clusters are surrounded by actin, suggesting that actin is the major component of the matrix present at these endocytic zones (28,29,56).…”
Section: Discussionmentioning
confidence: 63%
“…They also regulate a variety of proteins that control actin nucleation (13,25,26). Actin, in turn, is thought to play an important role in clathrin-mediated recycling by generating and organizing cytoskeletal scaffolds at endocytic zones (27)(28)(29) and, possibly, by contributing to the translocation of newly formed endocytic vesicles to the synaptic vesicle cluster (30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…Because control of actin polymerization is downstream of GEF activity, intersectin 1L may act as a switch that links actin polymerization to an input from the endocytic pathway. Although we do not yet know the exact role played by actin polymerization during endocytosis (Qualmann et al, 2000), there is remarkable colocalization of endocytic events and actin polymerization at the synapse (Dunaevsky and Connor, 2000), and both are tightly regulated by phosphatidylinositol biosynthesis (Cremona and De Camilli, 2001). Intersectin 1L, localized to peri-active zones Roos and Kelly, 1999), is thus well positioned to switch on actin polymerization in endocytic regions only after a burst of exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Actin and myosin are localized to presynaptic sites (Drenckhahn and Kaiser, 1983;Dunaevsky and Connor, 2000;Morales et al, 2000). In sympathetic neurons, inhibiting myosin II decreases synaptic transmission (Mochida et al, 1994;Takagishi et al, 2005), whereas in hippocampal neurons, MLCK inhibitors, 1-(5-iodonaphthalene-1-sulfonyl)-1H-hexahydro-1,4-diazepine⅐HCl (ML-7) and 1-(5-chloronaphthalene-1-sulfonyl)-1H-hexahydro-1,4-diazepine⅐HCl (ML-9), reduce the access to the reserve SV pool during repetitive stimulation (Ryan, 1997).…”
Section: Introductionmentioning
confidence: 99%